Nutritional Education for Mothers of Toddlers below the Red Line in Batoh Banda Aceh - Nanda Azalia Annisa; Saiful Bakri; Silvia Wagustina; Yulia Fitri (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
A mother's knowledge of nutrition affects their behavior in rearing their children. A factor that influences the nutritional status of children is a mother's behavior in choosing and providing food. A mother's behavior affects her ability to meet the family's food supply, consume food based on the right nutritional rules, choose the type of food, and prioritize the food for her family. Mother's poor behavior can be caused by her insufficient level of knowledge about nutrition and insufficient ability to apply it in daily life. This research aims to determine the effect of pocketbooks on the nutritional knowledge of mothers of toddlers whose nutritional condition is below the red line. This research employed a pre-experimental design, namely one group pretest-posttest. The research subjects were mothers of children whose nutritional condition is below the red line. Moreover, this study employed a total sampling technique with inclusion criteria, and the number of samples was 28 people. The statistical test using the independent T-test has obtained a p-value = 0.000 (< 0.05). Meanwhile, the measurement results show that the question of